2009
DOI: 10.1211/jpp/61.08.0006
|View full text |Cite
|
Sign up to set email alerts
|

Organic anion transporting polypeptide 2-mediated uptake of paclitaxel and 2'-ethylcarbonate-linked paclitaxel in freshly isolated rat hepatocytes

Abstract: The findings have provided an important step towards identifying a key transporter in hepatic detoxification of paclitaxel and TAX-2'-Et in small animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The observed trend indicating more Pgp activity in rodents compared to human studies would in this case be even more pronounced. Uptake transporter activity potentially differs between species and could become important when compounds would be substrates such as paclitaxel which is described to be a substrate for hepatic OATP2B1 (Tanino et al 2009). However, species differences in uptake transporter activity are unknown and for most Pgp substrates reported here, no BBB uptake transporter activity has been described.…”
Section: Discussionmentioning
confidence: 99%
“…The observed trend indicating more Pgp activity in rodents compared to human studies would in this case be even more pronounced. Uptake transporter activity potentially differs between species and could become important when compounds would be substrates such as paclitaxel which is described to be a substrate for hepatic OATP2B1 (Tanino et al 2009). However, species differences in uptake transporter activity are unknown and for most Pgp substrates reported here, no BBB uptake transporter activity has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Mrp3 mRNA in wild-type mouse liver, but not in PXR-null mice. [32] Other studies also showed that PCN increased oatp2 protein level in hepatocytes, [33,34] regulated the expression of organic cation transporters in rats [35] and UDP-glucuronosyltransferases mRNA expression in the liver. [36] We have noted that the UA was the substrate of OATPs/Oatps in one of our previous study.…”
Section: Metabolism Kinetics Of Uamentioning
confidence: 95%